Forensic Multidisciplinary Analysis in Battered Child Syndrome: Integrating Bruise Age Determination, Autopsy, and Imaging for Accurate Diagnosis - Indahty Purnamaningsih, Sari Nur; Bumi Agung, I Gusti Lanang; Yudianto, Ahmad; Jassey, Babucarr; Purwaningsih, Eni (International Journal of Medical Toxicology and Forensic Medicine, 2025)
Background: Battered Child Syndrome (BCS) is a grave medicolegal illness caused by repeated physical violence, usually resulting in severe injury or fatality. It is essential to differentiate the abuse injuries from other medical illnesses, such as coagulation disorders or metabolic bone disorders, that can mimic the pattern of injury. Case Presentation: A two-year-old boy was found dead under his mother’s boyfriend’s care. The investigation included a clinical history assessment, external examination, autopsy, histopathology, forensic imaging, and differential diagnosis. Relatives, medical professionals, and police gave the clinical history. External examination provided bruises of multiple colors; autopsy provided rib fractures, subdural hematoma, pulmonary contusions, and organ damage. Histopathology confirmed injuries of different ages, while forensic imaging (X-ray, CT scan, UV/IR photography) detected fractures in the skeleton and hidden bruises. Multidisciplinary assessment disclosed overwhelming evidence of recurrent NAT in accordance with BCS. Shaken baby syndrome, Munchausen syndrome by proxy, sudden infant death syndrome, coagulopathy, and metabolic bone disease were excluded as differential diagnoses. Conclusion: The case in question underscores the crucial importance of multidisciplinary forensic evaluation in distinguishing between abuse and medical illness. Reports require alterations to regular procedures, increased clinical suspicion, and system intervention for vulnerable children.